On Stock Return Patterns Following Large Weekly Price Movements: The Case of Hong Kong - LU, Yue (Institutional Knowledge at Singapore Management University, 2009)
In this paper, I examine the short-run and long-run performance of the largest 49 stocks in Hong Kong market which experience weekly price movements of more than ±10% between 1999 and 2007. For both decline and increase events, one-week significant reversal is documented. But such reversal in returns diminishes very quickly within two or three weeks. From a long-run perspective, I find that large price increases are followed by negative performance, which is consistent with the overreaction hypothesis. However, large price declines are also followed by negative cumulative abnormal returns, which supports the underreaction hypothesis. Such findings indicate that the reaction of investors in the Hong Kong market is marked by a distinct asymmetry. Generally, investors in Hong Kong overreact to good news and underreact to bad ones, which is in support of the overoptimism hypothesis. Furthermore, for decline (increase) events, underreaction (overreaction) is documented to be stronger for larger firms and glamour firms than for smaller firms and value firms.